Employing Modern Technologies in Contemporary Interior Spaces - Ahmed Sultan Kalaf; Lilian Ali Ajaj (Journal of Techniques)
The technological revolution and its technical products are among the most important influences that contributed to the dynamic change of societies, and new methods, skills and materials have brought about a major transformation in the design of interior spaces after they replaced their traditional counterparts. Employing modern technologies in the design of contemporary interior spaces, as well as setting the goal of the research as (determining how to employ modern technologies in contemporary interior spaces). The objective limits of the research included the study of digital technology, laser technology, and modern materials in the design of the interior spaces of historical museums. The theoretical framework of the research consists of three sections, the first of which dealt with the concept of technology, techniques and modern materials in interior design, the second dealt with the concept of contemporary interior space and its elements, and the third dealt with the concept of the museum, its types and design considerations. In the procedural aspect of the research, the descriptive approach was adopted in the analysis of the research sample, which consisted of five models from historical museums that were deliberately elected according to the goal of the research. The analysis process resulted in a number of results, the most important of which are: the integration of three-dimensional displays and interactive screens with the horizontal and vertical levels of space, the employment of hologram technology in the process of displaying holographic holdings.